If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -10 = 3y + -7 Reorder the terms: -10 + 6y = 3y + -7 Reorder the terms: -10 + 6y = -7 + 3y Solving -10 + 6y = -7 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -10 + 6y + -3y = -7 + 3y + -3y Combine like terms: 6y + -3y = 3y -10 + 3y = -7 + 3y + -3y Combine like terms: 3y + -3y = 0 -10 + 3y = -7 + 0 -10 + 3y = -7 Add '10' to each side of the equation. -10 + 10 + 3y = -7 + 10 Combine like terms: -10 + 10 = 0 0 + 3y = -7 + 10 3y = -7 + 10 Combine like terms: -7 + 10 = 3 3y = 3 Divide each side by '3'. y = 1 Simplifying y = 1
| 5x+4=80 | | x-2+3x+7=80 | | 95-x=30 | | F(x)=x^2(108-4x) | | x^2+y^2-10x+6y=15 | | 9=y^2-5 | | 26(y^2-5y+6)=0 | | (4k+5)(k+1)=1 | | 13x+17=6x+66 | | y=3+sqrt(y^2-5) | | 12x+6=5x+76 | | -x+12=3x-12 | | -8x-7=-5x-13 | | .5x+12.3=7.1-1.1 | | 3x+21=2x+17 | | 4x^3+22=7 | | -5x+12=-x+32 | | -3x+6=-2x+7 | | -5x+15=-4x+12 | | 3x-14=6x-38 | | 28-(-3)*(-7)= | | 37.5=x^3 | | 5x-6=-x+6 | | 22x+4+35x+5=180 | | 1-x^2=-7-3 | | (x-3/4)^2 | | 2x+23+2x+23=8x | | 4.5*X=13.5 | | 360=(6x-4)+(2x+8)+(2x+8)+(6x-4) | | abe=126 | | Z+8=(-5) | | 2y-6+y=y-1 |